It is not Black and White: A comparison of skin tone by playing position in the Premier League and English football - Van der Graaff, E.; Hoozemans, M.; Pasteuning, M.; Veeger, D.; Beek, P. J. (International Journal of Sports Science & Coaching, 2018)
Within the present manuscript we explore the role of skin tone on playing position within English football`s top four professional leagues. Player data (n=4515) was collected across five seasons (2010-2015). Unlike previous research, results indicate a statistically significant, but arguable minor difference between the skin tones of those who play in central as opposed to wide positions. However, a one-way ANOVA highlights significant differences between skin tone and individual playing positions. Between league differences were, however, non-significant. Although mean skin tone is still darker for peripheral (i.e., wide) positions, the situation is more nuanced than first thought. Instead of segregating players by central versus peripheral roles, it appears that players of a darker skin tone occupy positions associated with athleticism and strength. In contrast, players of a lighter skin tone appear to fulfil positions requiring organizational skills and creativity.